Ultrasound-Assisted Extraction, Chemical Characterization, and Impact on Cell Viability of Food Wastes Derived from Southern Italy Autochthonous Citrus Fruits - Gabriele Carullo; Anna Ramunno; Eduardo Maria Sommella; Michele De Luca; Emilia Lucia Belsito; Luca Frattaruolo; Matteo Brindisi; Pietro Campiglia; Anna Rita Cappello; Francesca Aiello (MDPI AG, 2022)
Citrus fruits are one of the principal fruits used to produce juices. Over the years, these fruits have been recognized as new health-promoting agents. In this work, food wastes derived from autochthonous citrus fruits of Southern Italy, named Limone di Rocca Imperiale, Arancia Rossa Moro, and Arancia Bionda Tardivo from Trebisacce, were analyzed. After fresh-squeezing juice, peel and pomace were employed to obtain six different extracts using an ultrasound-assisted method in a hydroalcoholic solvent. The extracts were analyzed in terms of qualitative composition, antioxidant properties, and antiproliferative activity on MCF-7, MDA-MB-231, and BJ-hTERT cell lines. GC-MS and LC-ESI-MS analyses showed different compounds: of note, limonin-hexoside, neodiosmin, obacunone glucoside, and diacetyl nomilinic acid glucoside have been identified as limonoid structures present in all the samples, in addition to different polyphenols including naringenin-glucoside, hesperetin-O-hexoside-O-rhamnoside-O-glucoside, diferuloyl-glucaric acid ester, chlorogenic acid, and the presence of fatty acids such as palmitic, myristic, and linoleic acids. These extracts were able to exert antioxidant activity as demonstrated by DPPH and ABTS assays and, although at higher doses, to reduce the cell viability of different solid tumor cell lines, as shown in MTT assays.